Promoting nasi goreng as Indonesian cultural heritage: Harmony in taste, history and tourism aspects - Amiruddin, Achmad; Adi, Prakoso; Mulyani, Rizka; Chi-Ming , Hsieh; Hidayat, Serli Hatul (Hasanuddin University Food Science and Technology Study Program, 2024)
Culinary diversity, such as nasi goreng, which is easily found both at street food to luxury restaurants in Indonesia, is the most popular thing for foreign tourists. The development of nasi goreng over time has solidified its status as a globally recognized cultural and national identity of Indonesia. Recently, nasi goreng stands as a national dish, rivaling and surpassing other international delicacies in popularity and flavor. However, there is a pressing need to promote the unique characteristics of Indonesian nasi goreng globally to enhance the international appeal and boost regional tourism potential. This review aims to delve into the history, diversity and uniqueness of Indonesian nasi goreng, examining the role in enhancing local tourism and promoting Indonesia’s cultural heritage. Our study showed that although nasi goreng is served in the same way, each nasi goreng in Indonesia has unique characteristics depending on the characteristics of the region. The variation in complementary ingredients across different regions contributes to Indonesia’s rich diversity of nasi goreng types. The beauty of tourism is also present in all regions of Indonesia. Promoting Indonesian culinary tourism should expose various traditional Indonesian foods and promote the beauty of tourism from the origin of the food itself. Therefore, exploring the rich history and unique flavors of Indonesian nasi goreng not only highlights the essence of the nation's culinary heritage but also serves as a gateway to promoting Indonesia as a vibrant and enticing tourist destination on the global stage.